3D printing of soft grippers with multimaterial design: Towards shape conformance and tunable rigidity. (2022) - Yeong, Wai Yee; Goh, Guo Liang; Goh, Guo Dong; Lee, Samuel; Altherr, Jannick; Tan, Jingyuan; Campolo, Domenico
Abstract: Grippers with shape conformance and tunable rigidity are often achieved using a combination of soft and rigid structures made of different materials. These grippers are often known as soft grippers. In this review article, various gripper designs with shape conforming ability and stiffness tunability are discussed. In particular, the discussion mainly focuses on the advantages and limitations of each gripper design in terms of the shape conformance and the ease of manufacturability. Then, various 3D printing technologies that are capable of doing multimaterial printing have been introduced. The potential of multimaterial 3D printing of soft and smart grippers has been discussed.